The Effect of Non-Performing Loans (NPL) and Operational Costs to Operating Income (BOPO) on Core Capital with Return on Assets (ROA) as a Mediating Variable in Rural Banks (BPR) in the East Bekasi Region for the Period of 2019-2024 - Cecep Taofiqurrochman; Puji Rahayu; Ligardi Purnama Hasyim (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effect of Non-Performing Loans (NPL) and Operational Costs to Operating Income (BOPO) on core capital, with Return on Assets (ROA) as a mediating variable in Rural Banks (Bank Perkreditan Rakyat/BPR) in the East Bekasi region for the period 2019–2024. This research employs a quantitative approach using secondary data obtained from the annual financial statements of 21 rural banks, which are structured as panel data and analyzed using the pooled data method. The analytical method applied is path analysis using a multiple linear regression approach with the assistance of SPSS version 25. The analysis is conducted through two structural models: the first model examines the effect of NPL and BOPO on ROA, while the second model examines the effect of NPL, BOPO, and ROA on core capital. The results indicate that NPL and BOPO have a negative and significant effect on core capital. NPL does not have a significant effect on ROA, whereas BOPO has a negative and significant effect on ROA. Furthermore, ROA is proven to have a positive and significant effect on core capital. The mediation test results show that ROA acts as a mediating variable in the relationship between NPL and BOPO and core capital, indicating that the impact of credit risk and operational efficiency on rural banks' capital does not occur solely through direct effects but is also transmitted through profitability performance.